Pendayagunaan Citraan Dalam Teks Syair Surat Kapal Masyarakat Melayu Indragiri Versi Anang Kasim - Sri Rahayu (UIR Press, 2021)
ABSTRACT The pattern of image application used by poets in a literary work, especially the text of the ship's verse, can affect the quality of the text of the ship's verse. The messages to be conveyed through literary works must be creative so that they appear attractive to read and listen to, so special characteristics and patterns are needed, especially in the field of image itself, to make his work beautiful and attractive. There are many ways to enjoy, understand and appreciate the work of the author, one of which is to study the Utilization of Imagery in Anang Kasim's Version of the Syair Surat Kapal of the Indragiri Malay Community. Therefore, the aim of this study is to analyze and interpret the Utilization of Images in Anang Kasim's Version of the Syair Surat Kapal of the Indragiri Malay Community. This needs to be examined because the existence of a literary work can be seen from how the author packages his work so that he can create its own patterns and styles from the author's side. This research is descriptive with content analysis method. The data of this research are sourced from the book Syair Surat Kapal Masyarakat Melayu Indragiri Karya Dedi Iswanto 2007. The data studied were documented by reading, taking notes, then summarized and grouped based on the pattern of applying images in Anang Kasim's version of Anang Kasim's version of Syair Surat Kapal Surat Melayu Indragiri Community. Based on the author's observations, the text of Anang Kasim's version of the Syair Surat Kapal Melayu Indragiri version has a unique and distinctive pattern of application of imagery utilization seen from the stylistic aspect, namely quality imagery so that readers are able to enjoy and interpret the express and implied meanings of the verse. Keyword: Utilization, Imagery, Syair Letters of the Ship